Prevalence of fetal alcohol syndrome in a population‐based sample of children living in remote Australia: The Lililwan1 Project. (15th January 2015) - Fitzpatrick, James P; Latimer, Jane; Carter, Maureen; Oscar, June; Ferreira, Manuela L; Carmichael Olson, Heather; Lucas, Barbara R; Doney, Robyn; Salter, Claire; Try, Julianne; Hawkes, Genevieve; Fitzpatrick, Emily; et al.
<x xml:space="preserve">Abstract</x> Aim Aboriginal leaders concerned about high rates of alcohol use in pregnancy invited researchers to determine the prevalence of fetal alcohol syndrome (FAS) and partial fetal alcohol syndrome (pFAS) in their communities. Methods Population‐based prevalence study using active case ascertainment in children born in 2002/2003 and living in the Fitzroy Valley, in Western Australia (April 2010–November 2011) (n = 134). Socio‐demographic and antenatal data, including alcohol use in pregnancy, were collected by interview with 127/134 (95%) consenting parents/care givers. Maternal/child medical records were reviewed. Interdisciplinary assessments were conducted for 108/134 (81%) children. FAS/pFAS prevalence was determined using modified Canadian diagnostic guidelines. Results In 127 pregnancies, alcohol was used in 55%. FAS or pFAS was diagnosed in 13/108 children, a prevalence of 120 per 1000 (95% confidence interval 70–196). Prenatal alcohol exposure was confirmed for all children with FAS/pFAS, 80% in the first trimester and 50% throughout pregnancy. Ten of 13 mothers had Alcohol Use Disorders Identification Test scores and all drank at a high‐risk level. Of children with FAS/pFAS, 69% had microcephaly, 85% had weight deficiency and all had facial dysmorphology and central nervous system abnormality/impairment in three to eight domains. Conclusions The population prevalence of FAS/pFAS in remote Aboriginal communities of the Fitzroy Valley is the highest reported in Australia and similar to that reported in high‐risk populations internationally. Results are likely to be generalisable to other age groups in the Fitzroy Valley and other remote Australian communities with high‐risk alcohol use during pregnancy. Prevention of FAS/pFAS is an urgent public health challenge.